Mango (Harum Manis) quality grading system - Mohd Mokhtar, Mohd Firdaus (2014)
Weight and size are the major parameters that the consumer identifies to be related to the grade of mango. According to Federal Agricultural Marketing Authority (FAMA) Malaysia, size of a mango is determined by weight. The mango named “Harum Manis” is a famous agricultural product of Perlis, Malaysia. To date, the farmers still rely manually on their visual inspection and experience to grade the mangoes into three sizes, i.e. A, B and C, where A is the largest mango, B is the medium and C is the smallest. This method is not consistent and erroneous amongst the farmers due to varying experience and human errors. Moreover, it becomes costly when more workers are needed. This paper investigates this issue and demonstrates a mechatronic system to grade the mangoes by weighing. The user could read the grade from a display. This method provides a consistent and easy-to-use solution to the farmer.